Order Blattodea. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Beccaloni, George; Eggleton, Paul (Zootaxa, 2013)
The Blattodea comprise the termites (epifamily Termitoidae only) and the cockroaches (all other taxa). 7570 living species of Blattodea are currently recognised, of which 2929 are termites (Krishna et al. 2013) and 4641 are cockroaches (Beccaloni 2007).